MEASURING THE NATIONAL ZAKAT INDEX (NZI) ON ZAKAT PERFORMANCE IN BOGOR REGENCY - Hilmiyah, Ulfah Laelatul; Beik, Irfan Syauqi; Tsabita, Khonsa (Journal of Islamic Monetary Economics and Finance, 2018)
Poverty is the most crucial problem in many countries including Indonesia. As a predominantly Muslim countries, there are several Islamic instruments to combat poverty, such as zakat. It is an act of worship that combines economic, social, moral and religious components to improve the welfare of Muslims, as well as reducing poverty. Bogor Regency, a region in Indonesia, targeted 10 billion rupiah as its zakat collection for 2016. However, the actual zakat collection was only 5 billion rupiahs, which signals the ineffectiveness of zakat management from either collection, distribution, or utilization. The purpose of this research is to analyse zakat performance in BAZNAS (Badan Amil Zakat Nasional; National Board of Zakat) in Bogor Regency. Data were collected through interviews and questionnaires completed by 100 mustahik household in Bogor Regency. The National Zakat Index was used with a calculation method called the Multi-Stage Weighted Index. The findings indicate that the implementation of zakat performance in BAZNAS Bogor Regency is fairly good.